2021
DOI: 10.3390/ma14092442
|View full text |Cite
|
Sign up to set email alerts
|

Study of Cytotoxic Properties of an Experimental Preparation with Features of a Dental Infiltrant

Abstract: Microinvasive dentistry is based on the treatment of early carious lesions with the use of dental infiltrants. The commercially available Icon dental infiltrant does not contain any bacteriostatic component. An experimental preparation enriched with the missing component was synthesised. The aim of this study was to evaluate the cytotoxicity of the experimental preparation. Mouse fibroblasts of the L-929 lineage were used for the in vitro study. Cell morphology and viability were assessed. In the cytotoxicity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…In previous studies, the authors demonstrated that the inclusion of metronidazole in the experimental formulation allows for targeted activity against both anaerobic and oxygen-deficient organisms. The PMMAn—MTZ component demonstrates strong antimicrobial activity against Bacteroides , Fusobacterium , Eubacterium , Clostridium , Peptococcus , Peptostreptococcus , and protozoa [ 26 ]. Both the authors and a researcher, Zhang, assessed that the inclusion of an antibacterial component in the composition of a dental infiltrant could potentially inhibit the development of caries at the site of application [ 26 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In previous studies, the authors demonstrated that the inclusion of metronidazole in the experimental formulation allows for targeted activity against both anaerobic and oxygen-deficient organisms. The PMMAn—MTZ component demonstrates strong antimicrobial activity against Bacteroides , Fusobacterium , Eubacterium , Clostridium , Peptococcus , Peptostreptococcus , and protozoa [ 26 ]. Both the authors and a researcher, Zhang, assessed that the inclusion of an antibacterial component in the composition of a dental infiltrant could potentially inhibit the development of caries at the site of application [ 26 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…The PMMAn—MTZ component demonstrates strong antimicrobial activity against Bacteroides , Fusobacterium , Eubacterium , Clostridium , Peptococcus , Peptostreptococcus , and protozoa [ 26 ]. Both the authors and a researcher, Zhang, assessed that the inclusion of an antibacterial component in the composition of a dental infiltrant could potentially inhibit the development of caries at the site of application [ 26 , 55 ]. Clinically, this is of great importance because the exposed surface of root cement provides a site of plaque retention.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In other words, polymerized dental products break down over time and release un-polymerized components, exposing surrounding living tissues-especially the pulp-to potential noxious effects [8]. Traditionally used methacrylate chemicals described in in vitro studies indicate that methacrylate resins such as bis-GMA, UDMA, and TEGDMA cause the inhibition of DNA and protein synthesis in fibroblast cells and, at higher concentrations, may lead to cell death in the surrounding tissues [9]. In the cited in vitro study, the authors demonstrated that most of adhesive resins used in orthodontics and available on the European market release biologically harmful substances to the immediate environment [10].…”
Section: Introductionmentioning
confidence: 99%